'Who really speaks like that?' – Children's implicit and explicit attitudes towards multilingual speakers of Dutch. Issue 4 (2nd October 2021) - Dekker, S. V.; Duarte, J.; Loerts, H.
ABSTRACT: This study investigates children's explicit and implicit language attitudes in a highly diverse primary education. Set in the bilingual province of Fryslân, the Netherlands, the current research was carried out in the scope of the 3M-project ('More opportunities with multilingualism': Duarte & Günther-van der Meij, 2018a. A holistic model for multilingualism in education. EuroAmerican Journal of Applied Linguistics and Languages, 5 (2), 24–43. https://doi.org/10.21283/2376905X.9.153), wherein pupils' home languages are used as a resource to promote multilingualism and thereby facilitate learning. We examined socially significant language attitudes and children's stereotypes towards prevalent minority and migrant languages. Participants consisted of 93 pupils (aged 7–12). They completed questionnaires to assess their explicit attitudes towards majority, migrant and minority languages. Additionally, 137 pupils performed an Implicit Association Test (IAT) to measure the relative attitudes of standard Dutch versus (1) the regional minority language (Frisian) and versus (2) a salient migrant language (Moroccan Arabic). Questionnaire results show significantly lower ratings for Moroccan Arabic and 'other languages' compared to Dutch, English and Frisian. Implicit results revealed a larger and significant preference for Dutch over Moroccan-Dutch accents and a smaller, non-significant, preference for Dutch over Frisian accents. Our results suggest a need for primary schools to explicitly address issues related to children's attitudes towards different languages and accents.